Diagnosis of induction motors by analyzing the harmonics of stator currents (stator fault) - GHERBI Aimane; MOULA Khair Eddine; KANECH Toufik Lazhari (University of Shahid Hama Lakhdar - El Oued, 2024)
Diagnosing stator faults in induction machines plays a crucial role in ensuring the reliable operation of electrical systems. Stator faults lead to reduced motor efficiency, increased energy consumption, and in some cases, complete motor failure. Therefore, the use of spectral analysis and Fast Fourier Transform (FFT) is a fundamental analytical tool in diagnosing these faults. This technique converts signals from the time domain to the frequency domain, enabling the identification of characteristic fault frequencies that indicate specific issues in the stator. This work presents an experimental study of asynchronous machine faults (with and without faults). We proposed a method based on stator current harmonics of induction machines. This technique involves studying the effect of a short circuit on the induction motor, determining the relative sensitivity and the best harmonics for detecting stator faults to be used as indicators for fault diagnosis. This technique is widely applied across various industries to enhance motor reliability, operational efficiency, and maintenance strategies, ensuring continuous and cost-effective motor performance. يلعب تشخيص أعطال الجزء الثابت في الآلات الحثية دورًا حيويًا في ضمان التشغيل الموثوق للأنظمة الكهربائية. تؤدي أعطال الجزء الثابت إلى تقليل كفاءة المحرك، وزيادة استهلاك الطاقة، وفي بعض الحالات، تؤدي إلى فشل المحرك بالكامل. لذا يعد استخدام التحليل الطيفي وتحويل فورييه السريع (FFT) أداة تحليلية أساسية في تشخيص هذه الأعطال. تقوم هذه التقنية بتحويل الإشارات من المجال الزمني إلى المجال الترددي، مما يمكن من تحديد ترددات الأعطال المميزة التي تشير إلى مشكلات محددة في الجزء الثابت . يتناول هذا العمل دراسة تجريبية لأعطال الآلات غير المتزامنة )مع وبدون أعطال(. وقد اقترحنا طريقة تعتمد على توافقيات تيار الجزء الثابت لآلات الحث. تستند هذه التقنية إلى دراسة تأثير الماس الكهربائي على المحرك الحثي، حيث يتم تحديد الحساسية النسبية وأفضل التوافقيات لاستخدامها كمؤشرات لتشخيص أعطال الجزء الثابت. تُطبق هذه التقنية على نطاق واسع في مختلف الصناعات لتعزيز موثوقية المحركات، وكفاءة التشغيل، واستراتيجيات الصيانة، مما يضمن أداءً مستمرًا وفعالًا من حيث التكلفة للمحركات
Master's theses: specializing in Electrical Machines
Keywords: stator fault; diagnosis; time harmonics; Transform (FFT); induction machines; Fast Fourier; short circuit; عطل الجزء الثابت، تشخيص، التوافقيات الزمنية، تحويل فورييه السريع (FFT) ، الآلات الحثية، تشخيص، فورييه السريع، ماس كهربائي .